Papillary meningioma with a history of renal clear cell carcinoma and lung adenocarcinoma: a case report - Zhang, Jing (Int J Clin Exp Pathol, 2019)
Papillary meningioma is a rare subtype of malignant meningiomas. The case of papillary meningioma is extremely rarer than other tumors that may pose a diagnostic dilemma to the pathologist. Here we report a rare case of papillary meningioma following renal clear cell carcinoma and lung adenocarcinoma and suggest a useful indicator for accurate diagnosis. A 52-year-old female patient was diagnosed with renal clear cell carcinoma and lung adenocarcinoma two and half years ago, respectively. Four years ago, she presented with nausea, dizziness, and left ear pain when her headache was severe. The symptoms became progressively worse and more frequent, so she was subjected to left cerebellar craniotomy for resection of the tumor. On the basis of its morphologic and immunohistochemical features, the tumor was diagnosed as a papillary meningioma. Papillary meningioma needs to be differentiated from other intracranial tumors. Early diagnosis of papillary meningioma could significantly reduce the progression of subsequent invasion and mortality.